Bistable electrical switching and nonvolatile memory effects by doping different amounts of GO in poly(9, 9-dioctylfluorene-2, 7-diyl). Issue 13 (13th February 2018) - Xin, Ying; Zhao, Xiaofeng; Jiang, Xiankai; Yang, Qun; Huang, Jiahe; Wang, Shuhong; Zheng, Rongrong; Wang, Cheng; Hou, Yanjun
Abstract : The device shows different conductive behavior: electric bistable nonvolatile flash memory behavior and conductor behavior. Abstract : Poly(9, 9-dioctylfluorene-2, 7-diyl) (PFO) was synthesized under a Suzuki coupling reaction, and its structure was proved by Fourier transform infrared (FT-IR) spectroscopy, and hydrogen and carbon nuclear magnetic resonance ( 1 H-NMR and 13 C-NMR). A nonvolatile organic memristor, based on active layers of PFO and PFO:GO composite, was prepared by spin-coating and the influence of GO concentration on the electrical characteristics of the memristor was investigated. The results showed that the device had two kinds of conductance behavior: electric bistable nonvolatile flash memory behavior and conductor behavior. With an increase in GO concentration, the device has an increased ON/OFF current ratio, increasing from 2.1 × 10 1 to 1.9 × 10 3, a lower threshold voltage ( V SET ), decreasing from −1.1 V to −0.7 V, and better stability. The current remained stable for 3 hours in both the ON state and OFF state, and the ON and OFF state current of the device did not change substantially after 9000 read cycles.